1996
DOI: 10.1017/s0021859600075602
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of labelled phenylalanine into different blood fractions in the portal vein and cranial mesenteric vein of lambs

Abstract: SUMMARYFour lambs (mean 27 kg liveweight) offered 900 g/day lucerne chaff were prepared with catheters in the portal vein (PV), cranial mesenteric vein (CMV), femoral artery (FA) and abomasum. L-[2,6-3H]phenylalanine (Phe) and 14C-(Phe)casein were infused into the abomasum in separate experiments. Concurrent samples of blood from the PV, CMV and FA were prepared as four fractions: plasma, deproteinized whole blood, free Phe in deproteinized whole blood, and whole blood. Ratios of net label uptakes in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…Whatever the diet, PAA net release across the MDV was not significantly different from PDV net release; and, as observed in sheep fed fresh forage (13) , the small intestine was the main contributor to PAA net release across the PDV (56 %). Peptide contribution to MDV net release of essential AA was only 7-8 %, with this contribution being slightly lower than previously reported in sheep (14 %) (13) , and in lambs (up to 20 %) (21) . Urea transfer to the small intestine, and its contribution to urea net uptake across the PDV, decreased with pea extrusion, probably as a consequence of the decrease in blood urea concentration.…”
Section: Nitrogen Transactions Across the Mesenteric-drained Visceracontrasting
confidence: 62%
“…Whatever the diet, PAA net release across the MDV was not significantly different from PDV net release; and, as observed in sheep fed fresh forage (13) , the small intestine was the main contributor to PAA net release across the PDV (56 %). Peptide contribution to MDV net release of essential AA was only 7-8 %, with this contribution being slightly lower than previously reported in sheep (14 %) (13) , and in lambs (up to 20 %) (21) . Urea transfer to the small intestine, and its contribution to urea net uptake across the PDV, decreased with pea extrusion, probably as a consequence of the decrease in blood urea concentration.…”
Section: Nitrogen Transactions Across the Mesenteric-drained Visceracontrasting
confidence: 62%
“…Our preliminary study on peptide determination showed that the estimation of plasma PAA is largely affected by the sample preparation. The chemical deproteinization with SSA is known to leave small quantities of protein in the supernatant (Hubbard et al, 1988;Neutze et al, 1996), whatever the final concen- tration in SSA. That probably explains the large concentration of AA (7,160 M in the artery) attributed to plasma peptide by McCormick and Webb (1982).…”
Section: Discussionmentioning
confidence: 99%
“…erable contribution (65 to 85%) of PAA to PDV net flux of AA (FAA + PAA) has been observed in steers (Webb et al, 1992;Koeln et al, 1993;Seal and Parker, 1996). In sheep, large (90%; Webb et al, 1992), low (20% for Phe; Neutze et al, 1996), or nonsignificant (Backwell et al, 1997) contributions of PAA were reported. Furthermore, it seemed that PAA release in the portal vein of steers mainly originates from the non-mesenteric area (Webb et al, 1992;Seal and Parker, 1996).…”
Section: Introductionmentioning
confidence: 96%
“…At any rate, net flux of free amino acids appears to be low compared with peptide-bound amino acids in ruminants (Koeln et al, 1993;Webb et al, 1993;Han et al, 2001). Based on evidence that chemical deproteinization overestimates the peptide amino acid concentration in plasma (Bernard and Rémond, 1996;Backwell et al, 1997), it has been suggested that the high flux of peptides might be due to the procedure of sample deproteinization (Neutze et al, 1996;Backwell et al, 1997). Methods for measuring peptides have generally relied on the difference method, where amino acid analysis of deproteinized samples before and after acid hydrolysis has occurred, with the difference being attributed to peptides.…”
Section: Net Portal-drained Visceral Flux Of Peptidesmentioning
confidence: 99%